(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
This paper is an excerpt of a PhD Thesis in â€œArchitecture. Theories and projectâ€, presented at DiAP â€“ Department of Architecture and Project of Sapienza UniversitÃ di Roma in April 2012. Thesisâ€™ title: â€œAround the Sahara desert. Enduring Topographies between Architecture, Desert and Cityâ€: supervisors: professors Ludovico Micara and Raffaele Panella. In this short text we will examine scientific premises and limits concerning a broader field of study, the settlement mechanism around the Sahara desert, deepening the processus of landscape construction, to be intended as a complex relationship between religion, geography and human adapting ability.